Régimen jurídico de la educación universitaria privada en Uruguay - Sheppard Gelsi, Marcelo (2023)
This article analyses the legal regime of private university education in Uruguay, examining the relationship between the Constitution and the human person, cultural and teaching freedom, the principle of subsidiarity and university autonomy. At the same time, it summarizes the international instruments and laws relating to teaching and education in Uruguay, and then surveys the concepts of higher, tertiary and university education. Finally, it examines the regulations applicable to private university education.